Penerapan Pendekatan Saintifik Dengan Model Pembelajaran Problem Based Learning (Pbl) Untuk Meningkatkan Aktivitas Belajar Ekonomi Pada Siswa Kelas Vii B Di Mts N Surakarta 1 Tahun Ajaran 2015/2016 - Wulandari, Dwi Endah, Drs. Djumali, M.Pd (2016)
This study was aimed to improve the learning activity by applying of scientific approach with learning model of problem-based learning (pbl). This study was a classroom action research which was conducted in two cycles. The subjects in this study were teachers who provide action and the action recipients were students of class VII B of MTs N Surakarta 1 with total 38 students. The method of collecting data which used in this study were interviews, observation, field notes, and documentation. The techniques of data analysis used in this study were data reduction, data presentation, and data verification. The results showed that there were an increase in students' learning activities that can be seen from the indicators, namely: 1) The enthusiasm of students in learning before action was 39.47% and at the end of the action, it became 92.10%, 2) Student interaction with teachers before actions was 26.31% and at the end of the action, it became 81.57%, 3) Interaction between students before action was 26.31% and at the end of the action it became 84.21%, 4) cooperation groups prior actions 31.57% and at the end of the action becomes 92.10% , 5) Activities of students in a group discussion before action was 26.31% and at the end of the action it became 86.84%, 6) Enterprises of students in the following study before action was 39.47% and at the end of the action, it became 78.94%, 7) Student's participations in concluding the learning materials before the action was 23.68% and at the end of the action, it became 84.21%. Therefore, it can be concluded that the use of scientific approach with a learning model of problem-based learning (pbl) can increase the activity in learning economic for students class VII B of MTs N Surakarta 1.